ANALISIS PERBEDAAN TINGKAT KEPATUHAN WAJIB PAJAK DAN PEMERIKSAAN PAJAK SEBELUM DAN SESUDAH PENERAPAN PP NO. 46 TAHUN 2013 (Studi pada KPP Pratama Pasuruan) - Dewi Rahmawati; Bety Nur Achadiyah (Jurnal Akuntansi Aktual, 2016)
The level of obedience is the willingness of the taxpayers to fulfill their tax obligations that is appropriate with an applicable tax laws. Before paying the tax payable, the taxpayer have to calculate the amount of the tax payable. In this case there are calculations that inappropriate or incorrect, so the Tax Office (KPP) will held an inspection and issued the Tax Assessment Letter (SKP). This research is to observe the magnitude of the differences before and after application of goverment regulation No. 46 year 2013 of the level a tax obedience and tax audit rate. This study is a comparative research. The population is the entire taxpayer there are registered as taxpayers of goverment regulation No. 46 year 2013 and the sample is 863 of Taxpayer from the monthly report. Data in this research is a secondary data from sie PDI for taxpayer compliance’s data and from sie Service for tax audit’s data. For theanalysis were used Wilcoxon Signed Test. The result of the research is decreasing of the level of tax obedience in paying tax payable after goverment regulation No. 46 year 2013 was applied. However from the tax inspection, the ordinance can reduce the number of errors calculation of the tax payable bythe taxpayers. The limitedness of this research was able to see compliance formally only, can not figure materially compliance or state of actual taxpayer out.Keywords: Taxpayer Compliance, Tax Inspection, Goverment Regulation No. 46 of 2013, Pratama Tax Office Pasuruan.